Canonical Wnt pathway gene expression and their clinical correlation in oral squamous cell carcinoma - Marimuthu, Madhulaxmi; Andiappan, Manoharan; Wahab, Abdul; Muthusekhar, M; Balakrishnan, Anandan; Shanmugam, Sambandham (Indian journal of dental research, 2018)
Aim: The aim of this study is to explore the prognostic significance and clinicopathological correlations of the Wnt pathway genes in a cohort of surgically treated patients with oral squamous cell carcinoma (OSCC) patients. Settings and Design: A prospective genetic study on patients with OSCC was carried out during the period from July 2014 to January 2016. Informed consent from patients and institutional ethical approval for the study was obtained and the guidelines were strictly followed for collection of samples. Subjects and Methods: Clinical data and mRNA expression analysis of ten genes in the canonical Wnt pathway were evaluated and their relationships with clinical and demographic variables were studied in 58 tissue samples. Wnt-3a, β-catenin, secreted frizzled-related proteins sFRP-1, sFRP-2, sFRP-4, sFRP-5, Wnt inhibitory factor 1, dickkopf-1, c-MYC, and cyclin-D1 from cancer (n = 29) and normal (n = 29) tissue samples were investigated using quantitative reverse transcription-polymerase chain reaction. Statistical Analysis: Descriptive statistics were used to summarize the sample characteristics and clinical variables. If the data were normal, then parametric tests were used; otherwise, nonparametric alternatives were used. All the analyses were carried out using SPSS version 23.0 (IBM SPSS Inc., USA). Results: Expression of sFRP-1, sFRP-2, and sFRP-5 in control samples and expression of c-MYC and cyclin D1 in cancer samples showed statistical significance. Significant expression of Wnt3A was observed among patients who had recurrence and were deceased. Conclusion: Wnt3A, β-catenin, and cyclin D1 are recognized as key components of Wnt/β-catenin signaling. However, in this study, there was no significant expression of all the three genes in OSCC. The proto-oncogene c-MYC showed statistically significant upregulation in cancer tissue samples suggesting that the OSCC among South Indian population is primarily not mediated by the canonical Wnt signaling pathway.